Analysis Analysis of the Utilization of Digital Marketing as a Business Strategy in Cafes and Restaurantsof the Utilization of Digital Marketing as a Business Strategy in Cafes and Restaurants: Analisis Pemanfaatan Pemasaran Digital Sebagai Strategi Bisnis dalam Café dan Restoran - Rini Yulia Handayani; Naba Fahlan Yakub; Muhammad Rizal; Shofira Mufidah (Al-Muhasabah: Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
Nowadays, the marketing process has undergone many changes, especially in using information technology to implement digital marketing. The benefits of digital marketing are considered more efficient in terms of cost and wider in terms of reach with a variety of settings that can adjust the target market of the type of business they have. Café is a type of business specializing in providing customers with food and beverages. The café business can be categorized as part of the food and beverage service industry. Typically, cafes operate with a business model that focuses on serving coffee, tea, snacks, and sometimes heavier dishes, in a cozy and relaxed atmosphere. Meanwhile, a restaurant is a place of business that provides food and beverages to customers to enjoy at the location. Restaurants often offer a wide variety of dishes, from simple menus to gourmet dishes, and can have a variety of themes or concepts. Cafes and restaurants have some similarities although there are differences in concept and service. The main similarity between the two is that they are places to provide food and drink. Both cafes and restaurants need to do marketing and branding to attract customers and build their reputation in the market. This can include marketing related to price, image or appearance, and the type of food served using conventional marketing as well as digital marketing. With the continuous development of information technology and the increasing use of social media, a digital marketing strategy is considered necessary to be implemented by a café or restaurant with three stages of the process, namely reviewing the situation, setting goals and objectives, and formulating strategies.